2009
DOI: 10.1177/1352458508096872
|View full text |Cite
|
Sign up to set email alerts
|

Tried and tested: the psychometric properties of the multiple sclerosis impact scale (MSIS-29) in a population-based study

Abstract: The MSIS-29 is an acceptable, reliable, and valid method of recording quality of life. A significant relationship between higher physical impact scores of the MSIS-29 and higher Kurtzke EDSS values suggests that is may be of use in clinical trials to monitor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 22 publications
10
34
2
1
Order By: Relevance
“…The relationship between the physical and psychological impacts of MS measured via the MSIS-29 has been documented [25], [30], [31] and we have confirmed this in our cohort [28]. However, the MSIS-29 is not designed to distinguish between anxiety and depression and these conditions require specific courses of treatment and care.…”
Section: Introductionsupporting
confidence: 77%
“…The relationship between the physical and psychological impacts of MS measured via the MSIS-29 has been documented [25], [30], [31] and we have confirmed this in our cohort [28]. However, the MSIS-29 is not designed to distinguish between anxiety and depression and these conditions require specific courses of treatment and care.…”
Section: Introductionsupporting
confidence: 77%
“…Much like multiple previous studies using classical test theory methods in community-based populations, 1120 the current study using the SELECT clinical trial population found support for the internal consistency and test-retest reliability, construct validity, and responsiveness of the MSIS-29v1 longitudinally over 52 weeks in patients with RRMS.…”
Section: Discussionsupporting
confidence: 76%
“…Multiple investigations using traditional psychometric analyses based on classical test theory have been conducted to assess the psychometric properties of the instrument, providing evidence of the instrument’s reliability, validity, and responsiveness. 1120 …”
Section: Introductionmentioning
confidence: 99%
“…It has a physical and a psychological component and is transposed to a score out of 100, and higher scores reflect higher impact of MS. The scale has previously been found to be valid and reliable for use in PwMS, including in those with severe disabilities (Riazi et al, 2002, Riazi et al, 2003, McGuigan and Hutchinson, 2004, Gray et al, 2009). The Guy's Neurological Disability Rating Scale (GNDS) measures levels of disability across 12 categories including cognition, mood, speech, upper and lower limb function, and fatigue (Sharrack and Hughes, 1999).…”
Section: Outcome Assessmentmentioning
confidence: 99%